Counterion condensation in short cationic peptides: limiting mobilities beyond the Onsager-Fuoss theory - Wernersson, Erik; Heyda, Jan; Kubíčková, Anna; Křížek, Tomáš; Coufal, Pavel; Jungwirth, Pavel (Electrophoresis, 2012)
We investigated the effect of the background electrolyte (BGE) anions on the electrophoretic mobilities of the cationic amino acids arginine and lysine and the polycationic peptides tetraarginine, tetralysine, nonaarginine, and nonalysine. BGEs composed of sodium chloride, sodium propane-1,3-disulfonate, and sodium sulfate were used. For the amino acids, determination of the limiting mobility by extrapolation, using the Onsager-Fuoss (OF) theory expression, yielded consistent estimates. For the peptides, however, the estimates of the limiting mobilities were found to spuriously depend on the BGE salt. This paradox was resolved using molecular modeling. Simulations, on all-atom as well as coarse-grained levels, show that significant counterion condensation, an effect not accounted for in OF theory, occurs for the tetra- and nonapeptides, even for low BGE concentrations. Including this effect in the quantitative estimation of the BGE effect on mobility removed the discrepancy between the estimated limiting mobilities in different salts. The counterion condensation was found to be mainly due to electrostatic interactions, with specific ion effects playing a secondary role. Therefore, the conclusions are likely to be generalizable to other analytes with a similar density of charged groups and OF theory is expected to fail in a predictable way for such analytes.
Keywords: Oligopeptides; Sodium Chloride; Molecular Dynamics Simulation; Lysine; lysin; kationty; Electrophoresis, Capillary; počítačová simulace; elektroforéza kapilární; chlorid sodný; Arginine; Cations; Sulfates; sírany; elektrolyty; simulace molekulární dynamiky; oligopeptidy; Computer Simulation; Electrolytes; arginin